A highly sensitivity and anti-humidity gas sensor for ethanol detection with NdFeO3 nano-coral granules. (January 2022) - Sheng, Hao; Ma, Shuyi; Han, Ting; Yun, Pengdou; Yang, Tingting; Ren, Jiangfeng
Abstract: In this context, the NdFeO3 nano-coral granules were synthesized using a solvothermal method and calcination route, and the gas-sensing and anti-humidity property were systematically tested. The result illustrated that the as-prepared NdFeO3 based sensor exhibited an excellent gas-sensing character to ethanol, a high response value of 150, fast response/recovery time of 19/22 s and large detection range of 5–1000 ppm, and the selectivity and stability were discussed. As is well-known, high specific surface area and pore size sensitive material provide more reactive active sites and promote oxidation reaction of material surface; in addition, at operating temperature of 250 °C, the high porosity provide transmission path of gas diffusion and gasses can permeate interior of material, accordingly the gas-sensitive property is enhanced. Therefore, the specific surface area and pore size of the NdFeO3 were researched. In the end, a sensing mechanism of the NdFeO3 nano-coral granules sensor was discussed. In a word, a gas sensor with high gas sensitivity and anti-humidity property was synthesized and it has the potential to be a candidate for practical application. Highlights: The NdFeO3 nano-coral granules were synthesized using a solvothermal method and calcination route. The gas sensing performances of the NdFeO3 sensor to ethanol was investigated and exhibited an ultra-high response value. The anti-humidity property of the NdFeO3 sensor was discussed.